DESIGN OF INVENTORY STOCK INFORMATION SYSTEM USING LARAVEL FRAMEWORK WITH FIFO METHOD - Bagus, Bagus Laksono Yudo Atmojo; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
Toko Anugerah Rianto is a business engaged in retail, namely cosmetics since 2016, located in Rungkut, Surabaya. Of course, in running his business, the business owner has his own challenges in running it. Based on the results of interviews conducted with business owners, the obstacle in running their business is controlling the availability of stock in the warehouse. This obstacle is caused by the absence of recording incoming and outgoing goods so that stock-outs and inaccurate availability often occur. This problem causes consumers to wait for stock to be available. The purpose of this research is to design an inventory information system that can overcome the problems of the business being run. This design uses the Research and Development (R&D) method which consists of 4D (define, design, develop, disseminate). The stock inventory management method applied in this study is the First In First Out (FIFO) method where the first item in is the first item out to avoid expired goods. The result of this research is a website-based inventory information system that is a solution to the problems of Anugerah Rianto Store to support accurate data collection of incoming and outgoing goods.